LINGUISTIC PICTURE OF THE WORLD AS A BASIC ELEMENT INTERCULTURAL COMMUNICATION (Archive of Conferences, 2022)
The article analyzes current approaches to the definition of “linguistic view of the world” in terms of modern theory of communication. The purpose of the article is to determine the basic characteristics of the linguistic view of the world. To solve the problems posed, the following methods of sociolinguistic research are d: inductive-deductive method, method of comparative analysis and descriptive method. The special role of intercultural communication investigations in the language, aesthetic, historic, domestic and other aspects is stressed, as well as the necessity for interdisciplinary dialogue of linguists, sociologists, psychologists, ethnologists, pedagogues and experts in the field of theory of communication